The elements of liberal feminism in Ang Lee’s films: An analysis of the female cheracters and characteristics in Crouching Tiger, Hidden Dragon (2000) and Eat Drink Man Woman (1994) / Qiu Minchan - Qiu , Minchan (2021)
In recent years, Chinese films have shown a lack of attention to women. The hollowedout female images created in Chinese films are inconsistent with the real ones. With the development of China's economy, the economic status of women is constantly improving. However, the female images in the movies cannot meet modern Chinese women's spiritual and cultural needs. Director Ang Lee has created many female characters in his films: three-dimensional, realistic, and feminist consciousness. Chinese women in economic and social transformation can resonate with their roles, reflecting on how to deal with the contradiction between tradition and modernity under the background of tradition and modernity combining, and find a way out. It also provides references for Chinese film and television practitioners in shaping female characters. This dissertation summarizes the different characteristics of female characters with the changes in history and times since the film came to China. Taking the two films directed by Ang Lee, Crouching Tiger, Hidden Dragon, and Eat Drink Man Woman as examples, this dissertation analyzes the liberal feminist consciousness of six female characters. They pursue the equal right of men in education and work, pursue freedom of marriage and love, pursue woman's right of self-determination, as well as the right to resist the patriarchal system. The growth experience under the eastern and western living and studying background, and the two influential women in his life- his mother and his wife, are the inspiration sources for director Ang Lee to create female characters with a feminist consciousness. At the same time, this dissertation also analyzes the characteristics of Ang Lee's female characters from the perspective of tradition and modernity. The female characters in Crouching Tiger, Hidden Dragon are "modern women" living in the traditional society. In contrast, the female characters in Eat Drink Man Woman are women who live in modern times but return to tradition finally. In addition, this dissertation analyzes Ang Lee's use of plots, lens, clothing, makeup, and other film means to create female characters, which show the feminist consciousness of female characters, which has particular reference significance for other directors to create female characters.